Harnessing stromal vascular fraction-based therapies for wound healing: Mechanisms, synergies, and clinical translation - Jing Wu; Yao Wang; Wenjie Chen; Min Lin; Jinwen Jiang; Hongde Jiang; Zehuan Li; Kailei Xu; Bin Zhang (Regenerative Therapy)
Wound healing remains a major challenge in contemporary medicine, particularly with the increasing incidence of chronic wounds, such as those associated with diabetes and thermal injuries. Current treatments such as vacuum sealing drainage, topical therapies, and autologous skin grafting are limited by issues like poor therapeutic efficacy, frequent dressing changes, and immune responses. Cell-based therapies have shown promise but are hindered by single-cell type limitations and hostile wound microenvironments. The stromal vascular fraction (SVF) has emerged as a potential solution, where the enzymatic digestion (E-SVF) contains various cell types, including adipose-derived stem cells (ADSCs), endothelial cells, and fibroblasts, while mechanical digestion (M-SVF) introduces additional extracellular matrix (ECM), termed stromal vascular matrix (SVM). This review systematically evaluates the applications of SVF and SVM in wound healing. SVF promotes wound repair through proangiogenic, immunomodulatory, and ECM remodeling effects. When combined with platelet-rich plasma (PRP) or biomaterials, its efficacy is further enhanced through the synergistic regulation of inflammation and angiogenesis. SVM, with preserved ECM, and SVM-conditioned medium (SVM-CM), rich in growth factors, demonstrate superior wound healing capabilities compared to conventional SVF. Despite the challenges posed by impaired viability and function of aged SVF-derived ADSCs and the low mechanical properties of SVM, emerging technologies, such as 3D cell cultures to enhance stemness and the integration of other biomaterials to improve mechanical strength, offer promising solutions. This review highlights the potential of SVF as an autologous, multifunctional strategy to address unmet needs in wound healing and provides insights into future clinical applications and research directions.